Direct and indirect assistance and motivation: How do they affect learning handstand skills? - Jasman, Niningnawati; Syahara, Sayuti; Syahrastani; Padli; Setiawan, Yogi (Journal Sport Area, 2024)
Background Problems: The level of skills at this time is optimally needed, especially for students because it can be a selling point for them, but the skills of these students are still very underestimated because there has been no innovation to find out the skill level of current students. Research Objectives: The purpose of this research is to determine the effect of direct and indirect assistance and learning motivation on handstand skills. Methods: This research model is a quasi-experiment with a factorial design with 2 x 2 levels. The population of this study was 106 people, and the sample size was 40 people using the ordinally mathematical pairing technique. Collecting data on learning motivation using a questionnaire and handstand skills using a handstand skills test. Data were analysed using a two-way ANOVA at a significance level of α = 0.05 and the Shapiro-Wilk Sig normality test > 0.05. Furthermore, because no interaction was found between assistance with motivation and handstand skills, the Tukey test was not carried out. Findings and Results: The results of the data analysis show: (i) Overall, there is no difference in the influence of assisted handstand skills; (ii) There is no interaction between assistance and learning motivation on handstand skills; and (iii) Directly assisted handstand skills are no better than indirect assistance in learning. high learning motivation group, (iv) Indirect assistance handstand skills were better compared to direct assistance in the low learning motivation group. Conclusion: These findings are important because they provide information about handstand skills in the form of assistance that may be useful for teachers and students in improving handstand skills. This research shows that there is no significant difference between direct and indirect assistance in improving handstand skills. The recommendation for future research is to expand the sample and consider individual factors among students.